The Edinburgh companion to Globalgothic - Duncan, Rebecca, Dr (Edinburgh companions to literature and the humanities., 2023)
"The Edinburgh Companion to Globalgothic is the most substantial exploration to date of gothic fiction in the international context. Examining texts from across six continents, the volume considers how gothic imagines, colludes with or interrogates relationships and phenomena that are planetary in scale. Accordingly, chapters address gothic engagements with - among others - resource imperialism, (ongoing) colonial history, diasporic identity, buckling economic unions, the rise of the internet, enthnonationalism, and entangled systems of gendered, racialised and ecocidal power. In this way, the collection moves decisively beyond the framework of globalisation to identify a range of new globalgothic approaches and modes, overall demonstrating that gothic is a key - though sometimes complicit - register for negotiating the challenges and histories of our uneven global present." --